Investment Trends for Iraqi Industries in Terms of Clean Production (selected model) - AL-Munim, Mohanad Ali Hussein; Abdul hameed, Manahel Mustafa (Journal of Economics and Administrative Sciences, 2021)
Industrial Investment according to Clean Productive methods is an important element in the process of rational use of Economic Resources, and the Iraqi industrial sector relied on traditional production methods; the productive activities in this sector did not take into consideration the environmental dimension, which leads to achieving the optimal use of economic resources, so it was necessary to have new investment trends heading with Clean Production. Therefore, the research is based on the hypothesis that "Clean Production contributes to improving the environment and rational use of Natural Resources." Based on the descriptive - inductive analysis methodology that study of Iraqi industries with Clean Production, and by seeking to collect the largest number of data and information related to these industries in order to obtain results and test the research hypothesis. The research concluded that despite the orientation of some Industries in Iraq towards Clean Production, they do not seek to achieve Sustainability in economic resources. For this, the researchers concluded that it is necessary to work seriously in harnessing technology, applied and technical sciences to direct Industrial Investment in Iraq towards Clean Products, by finding industrial alternatives that involve Cleaner Production and compensating for the inputs with Environmental damage. Research paper; Technical paper; Conceptual paper; Case study